The new Keynesian Phillips curve: Does it fit Norwegian data? - Pål Boug; Ådne Cappelen; Anders R. Swensen (Statistics Norway, Research Department, 2011)
We evaluate the empirical performance of the new Keynesian Phillips curve (NKPC) for a small open economy using cointegrated vector autoregressive models, likelihood based methods and general method of moments. Our results indicate that both baseline and hybrid versions of the NKPC as well as exact and inexact formulations of the rational expectation hypothesis are most likely at odds with Norwegian data. By way of contrast, we establish a well-specified dynamic backward-looking imperfect competition model (ICM), a model which encompasses the NKPC in-sample with a major monetary policy regime shift from exchange rate targeting to inflation targeting. We also demonstrate that the ICM model forecasts well both post-sample and during the recent financial crisis. Our findings suggest that taking account of forward-looking behaviour when modelling consumer price inflation is unnecessary to arrive at a well-specified model by econometric criteria.
Keywords: C51; C52; E31; F31; 330; The new Keynesian Phillips curve; imperfect competition model; cointegrated vector autoregressive models (CVAR); equilibrium correction models; likelihood based methods and general method of moments (GMM).